Small-scale cogeneration handbook - Kolanowski, Bernard F. (River Publishers, 2022)
Cogeneration can now turn up to 90% of the fuel burned into usable energy ⁰́₃ compared to just 52% of the fuel typically burned in a local power plant and in a separate existing hot water heating system. The fifth edition of this comprehensive reference provides a wealth of information to assist you in evaluating the feasibility and potential benefits of cogeneration for your facility. Covered are recent regulatory developments and their impact, system selection and sizing, permitting requirements, operation and maintenance, financing, technology basics, micro turbines, absorption chillers, distributed generation, and numerous case histories. This new edition is updated with new material and comes with access to a useful program that can help determine the economic value of applying cogeneration for your clients⁰́₉ benefit.